2018
DOI: 10.5206/cjsotl-rcacea.2018.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Impact of a Weeklong Fall Break on Stress Physiology in First Year Engineering Students

Abstract: Canadian post-secondary institutions are increasingly introducing a fall break into their term calendars, with the stated goal of reducing student stress and improving academic success. We conducted a pilot study around the time of this fall break during which we collected saliva samples to measure the ratio of two metabolic hormones (cortisol and dehydroepiandrosterone (DHEA)) from first-year male engineering students in order to document possible changes in their stress levels before and after the break. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
6
1
Order By: Relevance
“…Certainly, students in our focus groups reported that they appreciated having the fall break as an opportunity to reduce stress, rest, and recover from a hectic start to the school year. At first consideration, this finding seems paradoxical in light of longitudinal survey results from the broader student population at our institution (see Poole, Khan, & Agnew, 2017;Poole, Khan, & Agnew, 2018;Khan, Poole, & Beaton, 2018), which revealed that perceived stress was significantly higher after the break than before it. However, discussions with focus group participants revealed underlying reasons for this and provided critical context regarding the student experience that was not available from more quantitative measures.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Certainly, students in our focus groups reported that they appreciated having the fall break as an opportunity to reduce stress, rest, and recover from a hectic start to the school year. At first consideration, this finding seems paradoxical in light of longitudinal survey results from the broader student population at our institution (see Poole, Khan, & Agnew, 2017;Poole, Khan, & Agnew, 2018;Khan, Poole, & Beaton, 2018), which revealed that perceived stress was significantly higher after the break than before it. However, discussions with focus group participants revealed underlying reasons for this and provided critical context regarding the student experience that was not available from more quantitative measures.…”
Section: Discussionmentioning
confidence: 78%
“…Given the increasing adoption of fall breaks, it is critical to investigate the broader impact and the efficacy of this as a stress-reduction intervention, so as to support the development of evidence-based policy in higher education. As such, we are a multi-institutional team of researchers examining the effect of the fall break on undergraduate students in an interdisciplinary fashion: by administering validated perceived stress scales and questionnaires exploring undergraduate stress (Poole, Khan, & Agnew, 2018), by assessing physiological indicators of stress in students (Khan, Poole, & Beaton, 2018), and by conducting semi-structured focus groups with students. The qualitative branch of the study (presented here) is particularly critical for fostering a deeper understanding of the experiences that students have surrounding the fall break (Schonfeld & Farrell, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…As such, the validity of these measures may be limited, for example, by inconsistent interpretations of valence statements (e.g., what constitutes "good" health), socially desirable responses (e.g., over-reporting frequency of exercise), or failures in memory. We have developed a protocol that may allow for validation of self-reported stress through tracking physiological correlates of stress (Khan, Poole, & Beaton, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…While Cramer and Pschibul (2017) may have found that perceived stress levels for those students who attended to coursework during the Fall Pause were lower when they returned (and, again, this was not the case for those who recreated and/or procrastinated), Khan et al (2018) and Poole et al (2017Poole et al ( , 2018 found that all students (i.e., those who did schoolwork and those who recreated) experienced marginally lower levels of stress upon their return (compared to those who did not have a Fall Pause). So, it is important to recognize that though there is some agreement here within the limited available literature, there also remains some disagreement.…”
Section: Resultsmentioning
confidence: 96%
“…More specifically, we are suggesting that an additional degree of skeptical caution might be in order when considering the limited number of journals from which these articles are located. Additionally, three of these studies (Khan et al, 2018;Poole et al, 2017Poole et al, , 2018 are from the same researchers and are seemingly related to the same research project. If these three studies are viewed in this way (i.e., as one), there remains even less literature to consider.…”
Section: Resultsmentioning
confidence: 99%